CHALLENGES IN LEARNING ENGLISH ONLINE DURING THE COVID-19 PANDEMIC ON NON-ENGLISH DEPARTMENT STUDENTS, UNDIKSHA - Utami, Herya Darma (Journal for Lesson and Learning Studies, 2022)
During the COVID-19 pandemic, online learning is a must in carrying out the learning process in order to break the chain of spreading the virus. The English course, as a general course for students who are not majoring in English Education Departmen in Undiksha, has also implemented an online learning system since 2 semesters ago. The English course is general/basic English (MKU) which aims to develop a personality where English is the medium of instruction. The purpose of this study was to identify and describe in detail the challenges faced by the students of non-English Education Department Undiksha in learning English online during the Covid 19 pandemic, so the research design used was descriptive qualitative. Data were obtained from 412 students majoring in non-English Education Department Undiksha, who took English courses. Data collection techniques used were questionnaire and interviews. The questionnaire was made in the form of a google form and filled out by respondents online, while the structured interview technique was carried out using the Zoom application. Data analysis activities are data reduction, data presentation, and drawing conclusions/verification.Â